Cyclic oxidation of AISI 316L stainless steel – influence of water vapour between 800 and 1000°C. (May 2014) - Buscail, H.; Rolland, R.; Perrier, S.
<x content-type="archive" xml:space="preserve">Abstract</x> At 800 and 900°C, 10 vol.-%H2O in air has little effect on the AISI 316L stainless steel oxidation under isothermal and cyclic conditions. The oxide scale is composed of Cr2O3 with a small amount of Mn1·5Cr1·5O4 at the external interface. Results show that water molecules or protons can modify the diffusion process in the scale and lower the oxidation rate. At 1000°C, a deleterious effect of water vapour on the scale structure is observed. In situ X-ray diffraction was used to analyse the oxide formation on AISI 316L specimens during isothermal oxidation at 1000°C in moist air. Results show that the breakaway oxidation is due to the iron oxidation starting after 31 h oxidation. This leads to an external Fe2O3 scale growth and an internal multilayered FeCr2O4 scale formation. In wet air, thermal cycling conditions lead to continuous weight losses at 1000°C, whereas the scale remains adherent in dry air.